High uniformity and high quantum yield quantum dot film and method for manufacturing the same
Patent Information
- Application Number
- KR1020250151708
- Authority / Receiving Office
- KR · KR
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2025-10-20
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2045-10-20
Smart Images

Figure 112025116858415-PAT00001_ABST
Abstract
Description
Technology Field
[0001] The present invention relates to a highly uniform, high quantum efficiency quantum dot film and a method for manufacturing the same. More specifically, it relates to a polydimethylsiloxane-based quantum dot film having high quantum efficiency through uniform dispersion and preventing aggregation of quantum dots by using a viscosity-reducing material, and a method for manufacturing the same. Background Technology
[0002] Colloidal semiconductor quantum dots (QDs) are attracting significant attention in various application fields, including light conversion, light harvesting, and lighting. Quantum dot-based light-emitting devices possess unique characteristics that allow for bandgap control by changing their size and shape, and they offer advantages as light sources due to higher conversion efficiency and better color purity compared to OLEDs. Consequently, quantum dots are considered an essential component for next-generation displays and high-efficiency solar cells.
[0003] In practice, quantum dots are primarily used as light-converting films for QLEDs that can be attached to existing devices. The light-converting properties of quantum dots enable the emission of various colors, ultimately contributing to the generation of white light. Conversely, the spectral clarity of quantum dots is used to filter conventional white light into specified wavelengths with high color purity, enabling a wider color gamut in displays.
[0004] Wavelength conversion films are generally manufactured by mixing quantum dots with various resins such as polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA), and polydimethylsiloxane (PDMS), and then curing them through UV irradiation or heat treatment. Commercially, 3M™ manufactures a three-layer quantum dot enhancement film (QDEF) in which the top and bottom layers act as a protective barrier to prevent the degradation of quantum dots from exposure to oxygen and moisture, and the middle layer is an acrylate polymer film in which quantum dots are embedded. However, this structure has disadvantages such as high manufacturing costs and reduced quantum efficiency due to structural complexity.
[0005] In contrast, PDMS protects quantum dots dispersed in a matrix from the environment without the need for an additional protective layer. Furthermore, it is mechanically flexible, highly transparent at visible wavelengths, thermally stable, non-toxic, and exhibits high light extraction efficiency. Due to these advantages, PDMS has recently garnered significant attention as a quantum dot embedding matrix polymer.
[0006] However, when quantum dots are mixed with PDMS during the film manufacturing process, they are unevenly dispersed due to the high viscosity of PDMS (5100 cP, Silgard 184). Consequently, the aggregation of quantum dots degrades optical properties, including luminescence efficiency and transparency, leading to a decrease in QY.
[0007] Therefore, there is a need to develop a new quantum dot film manufacturing technology that solves the problem of quantum dot aggregation caused by the high viscosity of PDMS, achieves uniform dispersion by utilizing viscosity-reducing materials, and thereby possesses high quantum efficiency and excellent optical properties. Prior art literature
[0008] Republic of Korea Registered Patent Publication No. 10-2701845 The problem to be solved
[0009] The present invention aims to solve the problems of the prior art as described above by providing a highly uniform quantum dot film that prevents aggregation of quantum dots and achieves uniform dispersion using a viscosity-reducing material.
[0010] In addition, the purpose is to provide a quantum dot film with high quantum efficiency and enhanced absorption in the UV and blue light regions through uniform quantum dot dispersion.
[0011] Furthermore, the purpose is to provide a method for manufacturing a quantum dot film that enables large-area manufacturing through a simple manufacturing process while possessing excellent optical properties and storage stability. means of solving the problem
[0012] The present invention provides a quantum dot film composition comprising: quantum dots; zinc stearate; hollow silica beads; polydimethylsiloxane (PDMS); and a viscosity reducing agent; wherein the viscosity of the PDMS is reduced by 50% or more by the viscosity reducing agent.
[0013] The above viscosity reducing agent may be ethyl acetate or hexamethyldisilazane (HMDS).
[0014] The above quantum dots may be quantum dots with a CdSe / ZnS core / shell structure.
[0015] The weight ratio of the above quantum dots, zinc stearate, and hollow silica beads may be 1:(3-8):(2-6).
[0016] The above hollow silica beads may have an average diameter of 20 to 60 nm.
[0017] The above quantum dots emit light at a wavelength of 600 to 650 nm, and the initial quantum efficiency may be 70% or higher.
[0018] The present invention also provides a method for manufacturing a quantum dot film, comprising: (1) synthesizing quantum dots; (2) mixing the quantum dots with zinc stearate and hollow silica beads and drying to produce quantum dot powder; (3) mixing polydimethylsiloxane (PDMS) with the quantum dot powder; (4) adding a viscosity-reducing agent to the mixture to reduce the viscosity of the PDMS; (5) dispersing the mixture; (6) molding the dispersed mixture to produce a film; and (7) curing the film.
[0019] Step (1) above can be performed by mixing CdO and zinc acetate with oleic acid and 1-octadecene, vacuum degassing at 100–200°C, heating to 280–350°C to prepare a transparent solution, and then injecting trioctylphosphine in which Se powder and S powder are dissolved into the transparent solution and reacting at 280–350°C for 10–30 minutes.
[0020] Step (2) above may involve mixing the quantum dots, zinc stearate, and hollow silica beads in a weight ratio of 1:(3-8):(2-6) and drying at 50-80°C for 12-48 hours.
[0021] The viscosity reducing agent in step (4) above may be ethyl acetate or hexamethyldisilazane (HMDS).
[0022] The present invention also provides a quantum dot film manufactured by the above manufacturing method.
[0023] The present invention also provides any one of a display backlight unit, a quantum dot light-emitting diode (QLED), a lighting device, and a wavelength conversion film for a solar cell as an optical device comprising the quantum dot film.
[0024] The present invention also provides a display device comprising a quantum dot film manufactured by the above manufacturing method. Effects of the invention
[0025] The present invention can provide a quantum dot film having high uniformity and high quantum efficiency by using a viscosity-reducing material.
[0026] The quantum dot film according to the present invention can achieve excellent uniformity by significantly reducing the standard deviation of quantum dot dispersion compared to conventional PDMS films when ethyl acetate is used.
[0027] The present invention can achieve improved luminescence characteristics through uniform dispersion of quantum dots.
[0028] The manufacturing method according to the present invention can significantly reduce viscosity and greatly improve the efficiency of the ball mill process.
[0029] The present invention can secure excellent thermal stability through the addition of hollow silica beads.
[0030] The quantum dot film according to the present invention can achieve a superior quantum efficiency preservation rate compared to conventional methods.
[0031] The present invention can reduce manufacturing costs and simplify the process by ensuring excellent environmental stability even without upper and lower protective layers. Brief explanation of the drawing
[0032] FIG. 1 is a schematic diagram of a high-efficiency quantum dot-polymer composite film manufacturing process according to the present invention. Figure 2 is a graph showing the change in luminescence characteristics according to quantum dot concentration and heat treatment. Figure 3 is a luminescence mapping image showing the uniformity of quantum dot distribution in different films. Figure 4 is a graph showing the transmittance characteristics of three types of quantum dot films. Figure 5 is a graph showing the emission spectra at different excitation wavelengths. Figure 6 is a graph comparing the quantum efficiency of each film. Specific details for implementing the invention
[0033] The present invention provides a quantum dot film composition comprising: quantum dots; zinc stearate; hollow silica beads; polydimethylsiloxane (PDMS); and a viscosity reducing agent.
[0034] The viscosity of the PDMS is reduced by more than 50% by the above viscosity reducing agent.
[0035] Quantum dots serve as the core photoactive component of the present invention, absorbing light and emitting light of a specific wavelength. Preferably, quantum dots with a CdSe / ZnS core / shell structure are used.
[0036] In the CdSe / ZnS core / shell structure, the CdSe core is responsible for light absorption and emission, while the ZnS shell protects the core, thereby enhancing quantum efficiency. This structure provides high quantum efficiency and excellent photostability.
[0037] The quantum dots used emit light at a wavelength of 600 to 650 nm, preferably at 625 nm. The initial quantum efficiency must be 70% or higher, preferably 80% or higher. The size of the quantum dots determines the emission wavelength and is generally in the range of a diameter of 2 to 8 nm.
[0038] Quantum dots are dispersed in chloroform in a colloidal state, and organic ligands such as oleic acid are bound to their surfaces. These ligands provide the dispersibility and stability of the quantum dots.
[0039] Zinc stearate is a multifunctional additive for surface stabilization and thermal stability improvement of quantum dots. The weight ratio of quantum dots, zinc stearate, and hollow silica beads is 1:(3-8):(2-6), and preferably 1:5:4.
[0040] Zinc stearate provides surface stabilization through dangling bond passivation on the quantum dot surface, minimizes performance changes even when stored at 80°C for 48 hours by improving thermal stability, contributes to UV absorption to provide additional photoprotection effects, enhances interfacial bonding strength between quantum dots and the PDMS matrix, and prevents the aggregation of quantum dots during the dispersion process.
[0041] Hollow silica beads improve the mechanical and thermal properties of the film as a heat resistance enhancer. The average diameter is 20 to 60 nm, preferably 40 nm.
[0042] The hollow structure offers the effects of film weight reduction due to low density, excellent dispersibility due to a high surface area, improved thermal stability through reduced thermal conductivity, and enhanced light extraction efficiency through light scattering.
[0043] Hollow silica beads were introduced to address the low thermal stability and durability issues of the PDMS matrix. Experimental results confirmed excellent thermal stability, with a change in luminescence intensity of less than 10% even when stored at 80°C for 48 hours.
[0044] PDMS (polydimethylsiloxane) serves as the basic matrix material of the present invention, acting to disperse and immobilize quantum dots. It has advantages such as mechanical flexibility, high transparency (over 90% in the visible light range), thermal stability (-55℃ to 200℃), non-toxicity, and high light extraction efficiency.
[0045] However, PDMS has a high viscosity (approx. 5100 cP, Silgard 184), which hinders the uniform dispersion of quantum dots. To solve this problem, a viscosity reducer is introduced.
[0046] The PDMS used can be a commercial product such as Dow Corning’s Sylgard 184, and consists of a prepolymer base and a curing agent. The mixing ratio is generally 10:1 (base:curing agent).
[0047] The viscosity reducer is a key component that enables uniform dispersion of quantum dots by reducing the viscosity of PDMS by more than 50%. Either ethyl acetate or hexamethyldisilazane (HMDS) can be used.
[0048] The mechanism of action of the viscosity reducer is to weaken the interactions between PDMS molecular chains, thereby increasing molecular mobility. This allows quantum dots to move more freely and be uniformly dispersed within the PDMS matrix.
[0049] The present invention also provides a method for manufacturing a quantum dot film, comprising: (1) synthesizing quantum dots; (2) mixing the quantum dots with zinc stearate and hollow silica beads and drying to produce quantum dot powder; (3) mixing polydimethylsiloxane (PDMS) with the quantum dot powder; (4) adding a viscosity-reducing agent to the mixture to reduce the viscosity of the PDMS; (5) dispersing the mixture; (6) molding the dispersed mixture to produce a film; and (7) curing the film.
[0050] (1) Quantum dot synthesis step
[0051] In this step, high-efficiency red quantum dots with a CdSe / ZnS core / shell structure are synthesized. 0.3–0.5 mmol of CdO, 3–5 mmol of zinc acetate, 3–6 ml of oleic acid, and 25–35 ml of 1-octadecene are mixed in a 100 ml three-necked flask and vacuum degassed at 100–200°C.
[0052] After degassing, fill with N₂ gas and heat to 280–350°C to obtain a clear solution of Cd(OA)₂ and Zn(OA)₂. Rapidly inject 2–4 ml of TOP containing 0.3–0.5 mmol of Se powder and 3–5 mmol of S powder dissolved therein, and grow at 280–350°C for 10–30 minutes.
[0053] After the reaction is complete, it is cooled to room temperature, purified three times with toluene, acetone, and methanol, and then dispersed in chloroform for storage. Finally, a quantum dot having a quantum efficiency of 70% or more that emits light at 600–650 nm is obtained.
[0054] (2) Quantum dot powder manufacturing step
[0055] Chloroform is removed from the purified quantum dot solution to produce a solid powder. Quantum dots, zinc stearate, and hollow silica beads are mixed in a weight ratio of 1:(3-8):(2-6) and stirred uniformly.
[0056] The mixed solution is dried in a fume hood at 50–80°C for 12–48 hours. Hollow silica beads are added to improve the thermal stability of the PDMS matrix, and after drying is complete, the mixture is ground in a mortar and pestle to produce a powder with a moisture content of 5% or less.
[0057] (3) PDMS mixing step
[0058] 50 to 80 mg of dried quantum dot powder is mixed with 25 to 35 g of PDMS prepolymer base. The PDMS base and the curing agent are first homogeneously mixed in a ratio of 8:1 to 12:1, and then stirred at a low speed while minimizing the introduction of air bubbles.
[0059] Quantum dot powder is added in stages to prevent abrupt changes in viscosity, and added in small amounts to ensure complete dispersion.
[0060] (4) Step of adding viscosity-reducing agent
[0061] The high viscosity (4000–6000 cP) of PDMS is reduced by more than 50% to enable uniform dispersion of quantum dots. 8–12 ml of ethyl acetate or 4–6 ml of HMDS is added.
[0062] Ethyl acetate has excellent compatibility with PDMS and evaporates easily during the subsequent curing process. After the addition of a viscosity reducer, the viscosity decreases by 75–85% to 200–300 cP.
[0063] (5) Mixture dispersion step
[0064] A PDMS-quantum dot mixture with reduced viscosity is homogeneously dispersed using a ball mill. Zirconia balls are used, and the weight ratio of balls to mixture is set to 8:1 to 12:1.
[0065] It is performed at a rotational speed of 150 to 400 rpm for 30 minutes to 2 hours, with intermittent cooling times to prevent temperature rise. After dispersion is complete, large aggregates are removed by passing the mixture through a fine sieve (150 to 250 mesh).
[0066] (6) Film forming step
[0067] The dispersed mixture is formed into a film using a blade coater. The coating thickness is set to 300–500 μm, and the speed of the blade coater is controlled to 3–25 mm / s.
[0068] The substrate is made of PET film or glass, and the surface is cleaned beforehand. To minimize the introduction of bubbles, a degassing process is performed in a vacuum chamber at a vacuum level of -0.6 to -0.9 bar for 3 to 10 minutes.
[0069] (7) Film curing step
[0070] The molded film is cured through stepwise heat treatment. Curing conditions are applied differently depending on the viscosity reducer used.
[0071] When using ethyl acetate: Sequential curing at 50–70°C for 3–5 hours, 80–100°C for 10–15 hours, and 50–70°C for 3–5 hours. When using HMDS: Sequential curing at 80–100°C for 10–15 hours, and 50–70°C for 3–5 hours.
[0072] During the curing process, the relative humidity is maintained in the range of 40 to 60 percent, and the process is carried out in a nitrogen atmosphere. Finally, a film is obtained with a thickness of 150 to 250 µm and a size of 20 × 15 cm² to 35 × 25 cm².
[0073] The present invention will be described in detail below through examples. The following examples are intended only to illustrate the present invention, and the present invention should not be interpreted as being limited by the following examples.
[0075] Red quantum dot synthesis
[0076] High-brightness and stable CdSe / ZnS (core / shell) quantum dots were synthesized, having a quantum efficiency of up to 80% at an emission wavelength of 625 nm and a narrow linewidth of less than 35 nm. 0.4 mmol (51.36 mg) of CdO, 4 mmol (733.84 mg) of zinc acetate, 4.5 ml of oleic acid, and 30 ml of 1-octadecene were mixed in a 100 ml three-necked flask and vacuum degassed at 150°C until the vacuum level reached 100 mTorr.
[0077] After degassing, the 3-neck flask containing the mixed solution was filled with N₂ gas and heated to 310°C to obtain a clear solution of Cd(OA)₂ and Zn(OA)₂. 3 ml of TOP, containing 0.4 mmol of Se powder and 4 mmol of S powder dissolved, was rapidly injected into the reactor. After injection, quantum dots were grown at 300°C for 20 minutes. Subsequently, the reactor was cooled to room temperature to stop the growth of the quantum dots.
[0078] The grown quantum dots were purified by adding 20 ml of toluene, acetone, and an excess of methanol (3 times). After purification, the samples were dispersed in chloroform for further use.
[0080] Quantum Dot-Polymer Film Manufacturing Process
[0081] A flexible film containing quantum dots was prepared using the steps shown in Fig. 1. The first step was the pulverization of purified quantum dots as shown in Fig. 1(a). In this step, a solution of purified quantum dots containing chloroform was mixed with zinc stearate and hollow silica beads in a ratio of 1:5:4 and stirred, after which the mixed solution was dried on a 60°C hot plate in a hood for more than 24 hours.
[0082] To address the low thermal stability and durability issues of PDMS, heat-resistant silica beads were included in the mixture during the quantum dot pulverization process and dried. After the drying process, the aggregated mixture underwent a primary grinding process using a mortar and pestle.
[0083] Next, PDMS, which is commonly used in the fabrication of flexible films, was prepared. As previously mentioned, since the high viscosity of PDMS frequently hinders the uniform dispersion of quantum dots, bis(trimethylsilyl)amine (HMDS) and ethyl acetate (EA) were also prepared to reduce viscosity. The quantum dot concentration was selected to optimize color conversion efficiency based on the observation that PL intensity saturates at 0.158 wt% for the EA film (see Fig. 2(a)).
[0084] As shown in Fig. 1(b), three dispersions were prepared using these materials: PDMS and quantum dot powder (PDMS film), quantum dot powder containing PDMS and HMDS (HMDS film), and quantum dot powder containing PDMS and EA (EA film). Here, the amounts of quantum dot powder and PDMS were maintained at 66 mg and 31 g, respectively (see Table 1). 5 ml of HMDS was added to the HMDS film, and 10 ml of EA was added to the EA film.
[0085] The PDMS matrix mixed under each condition underwent a secondary grinding process using a ball mill to improve the dispersion of quantum dots and prevent aggregation. It was discovered that adding HMDS or ethyl acetate to the PDMS solution lowered the viscosity, which was confirmed by observing that the ball milling process was successfully performed at higher rotational speeds for these solutions. Specifically, the viscosity measured by a spindle viscometer was 1189 cP for the PDMS solution and 249.6 cP for the PDMS-EA mixed solution, confirming a significant reduction in viscosity due to the addition of surfactants.
[0086] For the subsequent film formation process, a mixture of PDMS and quantum dots was passed through a fine sieve to remove large aggregates of quantum dots. As shown in Fig. 1(c), a blade coater was used to produce a film with a thickness of approximately 400 μm from the solution. Finally, each film was cured to form a flexible film with a thickness of approximately 200 μm.
[0087] The PDMS and EA films were cured sequentially at 60°C for 4 hours, 90°C for 12 hours, and 60°C for 4 hours. Since the HMDS film cannot be formed at relatively low temperatures from the solution, different curing conditions were used (i.e., sequentially at 90°C for 12 hours and 60°C for 4 hours). Through this process, films up to a size of 30×20 cm² were obtained.
[0088] Figures 1(d) and (e) are optical images of quantum dot films with and without exposure to laser light (wavelength 365 nm), clearly showing distinct photoluminescence behavior. The luminescence behavior persisted for at least 48 hours after film fabrication, suggesting that the fabrication process did not degrade the optical properties.
[0089] To evaluate whether this luminescence behavior persisted for a long time, changes in PL intensity (black squares, left y-axis) and transmittance at a wavelength of 360 nm (red circles, right y-axis) as shown in Fig. 2 were observed while maintaining the sample at an ambient temperature of 80°C for 48 hours, as shown in Fig. 2. The PL intensity decreased by up to 5% during the first 12 hours, then stabilized, showing a decrease of only ~5% during the following 36 hours. Similarly, the transmittance gradually increased, showing a change of ~6% compared to the fabricated film.
[0090] These small changes in the optical properties of QDEF at high temperatures confirm that silica beads successfully increase the thermal resistance of the PDMS-based matrix, making a significant contribution to preventing thermal damage to the quantum dots in QDEF. Additionally, it simultaneously protected the quantum dots from degradation caused by oxygen and moisture exposure, which was observed in commercial QDEF.
[0091] Experimental Example 1: Uniformity of Quantum Dot Distribution
[0092] To investigate uniformity, the PL intensity distribution of specimens cut from the films prepared above was measured using a custom-made confocal fluorescence microscope. Nine specimens measuring 50 µm × 50 µm were collected from random locations on each type of film (PDMS, HMDS, EA).
[0093] For each specimen, confocal PL intensity was mapped according to the pixel position of a QDEF with an emission wavelength of 625 nm. The excitation laser was 532 nm in wavelength, and sufficient light absorption was confirmed in the quantum dot, with a pixel size of 250 nm.
[0094] Figures 3(a)–(c) are representative PL intensity images of specimens from different films, showing clearly different uniformities. Since higher PL intensity corresponds to higher quantum dot concentrations with minimized aggregation, this observation demonstrates that quantum dot dispersion is significantly influenced by additional materials. In other words, in areas where PL intensity is higher than in other areas, the quantum dots are more concentrated and less aggregated, while in areas where PL intensity is lower than in other areas, the quantum dots are less concentrated or more aggregated.
[0095] For example, the EA film specimen exhibits the best uniformity in PL intensity images, showing that the quantum dots are more evenly dispersed than in other films.
[0096] To compare the degree of quantum dot dispersion, the standard deviation (SD) was calculated from individual PL intensity images of nine specimens. Figure 3(d) shows the mean SD (gray bar) and the deviation SD (black solid line) of each film. The former indicates PL intensity uniformity in a small area, while the latter indicates uniformity across the entire film.
[0097] Both the mean and deviation of SD are reduced in HMDS and EA films compared to PDMS films, confirming that dispersibility is improved when surfactants are applied. More importantly, EA films exhibit the best dispersibility, highlighting the excellent effect of EA in improving dispersibility by lowering viscosity. Additionally, because the deviation of SD in EA films is extremely small (1×10⁻⁶ -5 Good dispersibility persists throughout the entire film.
[0098] These findings suggest that the optical properties of quantum dot films can be significantly enhanced when surfactants are applied to improve the uniformity of the quantum dot distribution. To test this hypothesis, the absorption characteristics of the films were measured.
[0099] Experimental Example 2: Enhanced UV absorption of quantum dot films
[0100] Figure 4(a) shows the absorption spectra of the three different types of samples. In particular, the transmittance of all three films decreases significantly as the wavelength shifts from the visible light to the UV range, with the EA film decreasing by 20% at a wavelength of 350 nm, while increasing by 70% at a wavelength of 900 nm.
[0101] These significant changes in transmittance demonstrate that quantum dot films can act as UV protective materials, particularly protecting against UV-A, which damages biomolecules and prevents surface degradation of photovoltaic devices. Specifically, the EA film exhibited significantly reduced transmittance across the entire wavelength range compared to PDMS and HMDS films.
[0102] Compared to the transmittance of the PDMS film, the transmittance of the HMDS film decreased by about 10% in the UV range and about 2.5% in the visible and NIR ranges, whereas the transmittance of the EA film decreased by about 15% in the UV range and about 5% in the visible and NIR ranges.
[0103] To determine the contribution of additional materials such as HMDS and EA to the reduction in transmittance, films without quantum dot powder were prepared and their transmittance was observed. The results are presented in Figure 4(b) (hereinafter, the HMDS reference film and EA reference film, respectively). All films exhibited significantly high UV transmittances reaching 45-55% at 350 nm compared to the transmittance of the films containing quantum dots. This confirms the contribution of quantum dots to UV absorption.
[0104] However, a significant amount of UV light was also absorbed by additional materials. Specifically, since the PDMS reference sample exhibits a significantly lower transmittance than a typical PDMS film (typically ~80% at a wavelength of 250 nm), chemicals such as zinc stearate used during film pulverization also contribute to UV absorption. Additionally, the transmittance variation of each film indicates that added surfactants (HMDS and EA) also contribute to absorption. However, the contribution is within about 10%.
[0105] To determine the precise contribution of quantum dots in different films, the contributions of zinc stearate, HMDS, and EA were subtracted from the total transmittance of the PDMS, HMDS, and EA films. In addition, the difference in quantum dot concentration for the different films was considered. Relative absorption of quantum dots (A rel ) calculated as follows:
[0106] A rel = (1 - T film / T ref ) / C rel (1)
[0107] Here, Tfilm and T ref ε₀ is the thickness-normalized transmittance of the film shown in FIG. 4(a) and the reference film (shown in FIG. 4(b)), respectively. C rel represents the relative quantum dot concentration with respect to the quantum dot concentration of the PDMS film, and C rel,PDMS = 1, C rel,HMDS = 0.86, C rel,E.A. = 0.76.
[0108] Figure 4(c) shows A of various mixtures of quantum dots with PDMS, HMDS, and EA films extracted using this method. rel The values are shown. Absorption increases in HMDS and EA films compared to PDMS film. Specifically, the absorption of the EA film increases to a maximum of 0.7 at 350 nm, which is twice that of the PDMS film, demonstrating that the UV protection ability of the quantum dots has been significantly improved.
[0109] In addition, absorption at longer wavelengths (approx. 650-900 nm) does not show a significant difference between the EA and HMDS films, suggesting that the increase in absorption is dominated by the enhancement of the absorption characteristics of the quantum dots. This indicates that the absorption cutoff of CdSe / ZnS quantum dots with an emission wavelength of 632 nm is approximately 650 nm.
[0110] These results demonstrate that the increased dispersibility resulting from the addition of surfactants improved the absorption characteristics of quantum dots. Increased absorption in the UV region can lead to enhanced luminescence, as discussed in the following section.
Claims
Claim 1 A quantum dot film composition comprising: quantum dots; zinc stearate; hollow silica beads; polydimethylsiloxane (PDMS); and a viscosity reducing agent; wherein the viscosity of the PDMS is reduced by 50% or more by the viscosity reducing agent. Claim 2 A quantum dot film composition according to claim 1, wherein the viscosity reducing agent is ethyl acetate or hexamethyldisilazane (HMDS). Claim 3 A quantum dot film composition according to claim 1, wherein the quantum dots are quantum dots having a CdSe / ZnS core / shell structure. Claim 4 A quantum dot film composition according to claim 1, wherein the weight ratio of the quantum dots, zinc stearate, and hollow silica beads is 1:(3-8):(2-6). Claim 5 A quantum dot film composition according to claim 1, wherein the hollow silica beads have an average diameter of 20 to 60 nm. Claim 6 A quantum dot film composition according to claim 1, wherein the quantum dots emit light at a wavelength of 600 to 650 nm and have an initial quantum efficiency of 70% or more. Claim 7 (1) a step of synthesizing quantum dots; (2) a step of mixing the quantum dots with zinc stearate and hollow silica beads and drying to produce quantum dot powder; (3) a step of mixing polydimethylsiloxane (PDMS) with the quantum dot powder; (4) a step of adding a viscosity-reducing agent to the mixture to reduce the viscosity of the PDMS; (5) a step of dispersing the mixture; (6) a step of molding the dispersed mixture to produce a film; and (7) a step of curing the film; comprising a method for manufacturing a quantum dot film. Claim 8 A method for manufacturing a quantum dot film according to claim 7, wherein step (1) involves mixing CdO and zinc acetate with oleic acid and 1-octadecene, vacuum degassing at 100 to 200°C, heating to 280 to 350°C to produce a transparent solution, and injecting trioctylphosphine in which Se powder and S powder are dissolved into the transparent solution and reacting at 280 to 350°C for 10 to 30 minutes. Claim 9 A method for manufacturing a quantum dot film according to claim 7, wherein step (2) involves mixing the quantum dots, zinc stearate, and hollow silica beads in a weight ratio of 1:(3-8):(2-6) and drying at 50-80°C for 12-48 hours. Claim 10 A method for manufacturing a quantum dot film according to claim 7, wherein the viscosity reducing agent in step (4) is ethyl acetate or hexamethyldisilazane (HMDS). Claim 11 A quantum dot film manufactured by the manufacturing method of claim 7. Claim 12 An optical device comprising the quantum dot film of claim 11, wherein the optical device is any one of a display backlight unit, a quantum dot light-emitting diode (QLED), a lighting device, or a wavelength conversion film for a solar cell. Claim 13 A display device comprising a quantum dot film manufactured by the manufacturing method of claim 7.
Citation Information
Patent Citations
Preparation method and processing equipment of ultrathin quantum dot film
CN111793448A
Quantumdot film and optical memberusing the same
KR1020190009025A
Backlight unit and display device including the same
KR1020190009026A